2015
DOI: 10.1093/ckj/sfv008
|View full text |Cite
|
Sign up to set email alerts
|

What is new in the management of rapidly progressive glomerulonephritis?

Abstract: Rapidly progressive glomerulonephritis (RPGN) results from severe crescentic damage to glomeruli and leads to irreversible kidney failure if not diagnosed and managed in a timely fashion. Traditional treatment has relied on glucocorticoids and cyclophosphamide, with additional plasmapheresis for certain conditions. Here we describe updates in the management of RPGN, according to the underlying renal pathology. However, there remains a paucity of trials that have enrolled patients with more advanced renal disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 76 publications
(74 reference statements)
1
34
0
9
Order By: Relevance
“…Treatment for RPGN relies on supportive care, glucocorticoids and cyclophosphamide. Plasmapheresis is the standard treatment for anti‐GBM disease with favorable clinical outcomes, and an additional treatment for ANCA‐associated vasculitis, producing reduction in the risk of ESRD (relative risk, 0.64) . In this study, despite the increased rate of cyclophosphamide treatment and availability of plasmapheresis during 2008–2014, renal outcome was not different to the prior period (1997–2007).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Treatment for RPGN relies on supportive care, glucocorticoids and cyclophosphamide. Plasmapheresis is the standard treatment for anti‐GBM disease with favorable clinical outcomes, and an additional treatment for ANCA‐associated vasculitis, producing reduction in the risk of ESRD (relative risk, 0.64) . In this study, despite the increased rate of cyclophosphamide treatment and availability of plasmapheresis during 2008–2014, renal outcome was not different to the prior period (1997–2007).…”
Section: Discussionmentioning
confidence: 60%
“…Plasmapheresis is the standard treatment for anti-GBM disease with favorable clinical outcomes, and an additional treatment for ANCA-associated vasculitis, producing reduction in the risk of ESRD (relative risk, 0.64). [21][22][23] In this study, despite the increased rate of cyclophosphamide treatment and availability of plasmapheresis during 2008-2014, renal outcome was not different to the prior period (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007). This may be due to the low number of patients with anti-GBM disease or ANCA-associated vasculitis who received the treatment.…”
Section: Discussionmentioning
confidence: 88%
“…CGN, also known as rapidly progressive glomerulonephritis, is characterized by glomerular necroinflammation and crescent formation . Mulay et al have demonstrated that MDM2 drives CGN through both p53‐dependent and p53‐independent pathways.…”
Section: Roles Of Mdm2 In Inflammation and Autoimmune Diseasesmentioning
confidence: 99%
“…Importantly, when discussing RPGN, a number of entities are frequently included in case series and trials, thus confounding results . Therapy consists of administration of high‐dose corticosteroids (e.g., methylprednisolone) and cytotoxic immunosuppressive drugs (e.g., cyclophosphamide or azathioprine) . Other drugs used include leflunomide, deoxyspergualin, tumor necrosis factor blockers, calcineurin inhibitors, and antibodies against T cells .…”
Section: Nephrological Disorders: Rapidly Progressive Glomerulonephritismentioning
confidence: 99%
“…The following therapy recommendation is based on the few uncontrolled and controlled studies available . TA is indicated in combination with an immunosuppressive therapy with prednisolone (intravenous pulse therapy, or oral therapy), cyclophosphamide (intravenous pulse therapy or oral therapy), or azathioprine in indicated in the following cases: RPGN with serum creatinine under 5.8 mg/dL without oliguria in anti‐GBM disease All severe forms of RPGN with or without ANCA ab, like the pauci‐immune complexes, (Cr >6 or patient on dialysis) Goodpasture syndrome with life‐threatening hemoptysis, or diffuse alveolar hemorrhage from ANCA or MPA independent of renal function status Preparation for kidney transplant with anti‐basement membrane antibodies still detectable in the serum. …”
Section: Immune Complex Nephritismentioning
confidence: 99%